Sex Difference in the Association Between Eating Away From Home and the Risk of High Serum Uric Acid in South China - Chen, Shao-wei; Wang, Ping; Ji, Gui-yuan; Jiang, Qi; Hong, Xiao-min; Ma, Wen-jun; Huang, Rui; Chen, Zi-hui; Peng, Jie-wen (Frontiers in Nutrition, 2021)
Background: Prevalence of high serum uric acid is increasingly rising in recent years and diet behavior is perceived to be associated with high serum uric acid. This study aims to explore the relationship between eating away from home (EAFH) and the risk of high serum uric acid in adults in South China. Methods: Data utilized in this study was from Guangdong Nutrition and Health Survey (NHS) 2015. Serum uric acid concentration was detected. EAFH in the past week was investigated. We defined EAFH as food consumption away from home. Dietary data were collected by 24-hour recalls in 3 consecutive days. A generalized linear mixed effects model was applied to compute odds ratio (OR) and its corresponding 95% confidence interval (CI). Results: A total of 3489 individuals were included in this study. A 1.27-folds OR (95%CI: 1.05-1.52, P-value: 0.012) of high serum uric acid was identified in adults with EAFH in comparison of those without EAFH. With respect to men, a 1.66-folds OR (95%CI: 1.30-2.10, P-value: <0.001) of high serum uric acid was observed. We also observed that men with EAFH had higher intakes of red meat, poultry, vegetable, carbohydrate, protein, fat and total energy, while lower grain intake than those without EAFH. However, there was lack of significant association between EAFH and the odds ratio of high serum uric acid in women. Women with EAFH did not have higher consumptions of red meat, vegetable, fish, fat and water than those without EAFH. Conclusions: EAFH was found to be associated with an increased odds ratio of high serum uric acid in men, but not in women.